208k views
2 votes
Solve −4(x + 1) − 3 = −3(x − 4). (1 point) −19 19 2 0

User Bakudan
by
4.5k points

1 Answer

1 vote

Answer: x = -19

Explanation:

-4(x + 1) - 3 = - 3(x - 4). original equation

-4x -4 -3 = -3x + 12 distributed terms into the parentheses

-4x -7 = -3x + 12 added together terms (simplified terms)

-4x = -3x + 19 added term to the other side of the equation

-1x = 19 added term to the other side of the equation again

x = -19 divided by negative one

User Nguyen Manh Linh
by
4.7k points